2006
DOI: 10.1002/j.2161-1912.2006.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Normative and Behavioral Persuasion on Help Seeking in Thai and American College Students

Abstract: On the basis of previous research on self‐construals, the theory of reasoned action, and persuasive communication, the authors hypothesized that individual, behavioral‐focused information would be more effective in increasing help‐seeking intention among college students in the United States, whereas relational, normative‐focused information would be more effective among college students in Thailand. Results partially supported these predictions, suggesting that different information can enhance help‐seeking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
1
17
2
Order By: Relevance
“…A few other known studies with non-Western populations (Christopher, Skillman, Kirkhart, & D’Souza, 2006; Lee et al, 2015; Mo & Mak, 2009; Yeh, 2002) have implicated the role of self-construal within the differential cultural help-seeking processes. For example, Christopher et al (2006) examined help-seeking from two groups of participants in Thailand.…”
Section: The Contribution Of Cultural Context To the Traditional Helpmentioning
confidence: 99%
“…A few other known studies with non-Western populations (Christopher, Skillman, Kirkhart, & D’Souza, 2006; Lee et al, 2015; Mo & Mak, 2009; Yeh, 2002) have implicated the role of self-construal within the differential cultural help-seeking processes. For example, Christopher et al (2006) examined help-seeking from two groups of participants in Thailand.…”
Section: The Contribution Of Cultural Context To the Traditional Helpmentioning
confidence: 99%
“…There is evidence that persuasion based on different emphases in the message varies in its effect depending on culture. For example, a study amongst Americans (i.e., within an individualistic culture) found persuasion was most powerful when it focussed on the benefits of help‐seeking to the individual (Christopher, Skillman, Kirkhart, & D'Souza, ). In contrast, amongst Thai individuals (i.e., within a collectivist culture) persuasion was more powerful when it was based on whether help‐seeking would be approved or disapproved of by others in the family or community.…”
Section: Discussionmentioning
confidence: 99%
“…Self-construals may also have important implications for the marketing of counseling services on higher educational campuses. For instance, Christopher, Skillman, Kirkhart, and D'Souza (2006) found that a marketing message emphasizing social acceptance of counseling increased help-seeking intention more than a message outlining the personal benefits of seeking counseling did in a collectivistic society (Thailand) and that the message outlining personal benefits of counseling was more effective in increasing help-seeking intention among primarily White students in a more individualistic society (United States). This suggested that help-seeking on college campuses might be enhanced by including both individualistic and collectivistic language in the counseling center's literature.…”
Section: Implications For Practicementioning
confidence: 99%